Effects of substitution of dietary fish oil with a blend of vegetable oils on liver and peripheral blood leucocyte fatty acid composition, plasma prostaglandin E2 and immune parameters in three strains of Atlantic salmon (Salmo salar) - Petropoulos, Ioannis K; Thompson, Kimberly; Morgan, Alison L; Dick, James R; Tocher, Douglas R; Bell, J Gordon (Aquaculture Nutrition, 2009)
Duplicate groups of three genetic strains of Atlantic salmon smolts were cultured on diets containing either fish oil (FO) or a blend of vegetable oils (VO). Fatty acid compositions of liver and peripheral blood leukocytes were compared. The effect of different strains and diets on innate immune parameters and plasma prostaglandin E2 were also measured. Two strains were selected as being either “fat” or “lean” in terms of muscle adiposity. The third strain was a commercial stock (MH). Total replacement of dietary FO with VO resulted in reduced docosahexaenoic (DHA; 22:6n-3) and eicosapentanoic acids (EPA; 20:5n-3) in liver, while oleic (18:1n-9), linoleic (18:2n-6) and α-linolenic (18:3n-3) acids were all increased in VO-fed fish. Fatty acid compositions of blood leucocytes showed similar changes. Evaluation of innate immune function showed that in the fat strain circulating leucocytes were significantly lower in VO fish. The lean strain also had significantly higher serum lysozyme activity than MH fish. Reduced haematocrit was seen in VO lean fish compared to FO lean fish. This study provides evidence of strain-induced differences in liver and leukocyte fatty acid compositions and innate immunity in Atlantic salmon fed either FO or VO-based diets.